Reflection phenomena of waves in a semiconductor nanostructure elasticity medium. Issue 6 (2nd November 2021) - Adnan, J.; Ali, Hashmat; Khan, Aftab
ABSTRACT: This paper presents a coupled nonlocal elasticity theory and a three-phase lag model to study the reflection of thermo-elastic wave in a semiconducting nanostructure medium. The nonlocal elasticity theory and three-phase lag thermal conduction model are used to formulate the governing equations. A heat equation with a fractional order is incorporated to study thermal effects on the propagation of the wave. Governing equations are decomposed into longitudinal and transverse components using the decomposition method. It is observed that four waves are propagating in the medium, in which three are longitudinal waves and one is a transverse wave. The reflection coefficients of the reflected waves are obtained analytically and are presented graphically for a particular material. The effects of the nonlocal parameters e 0 a, and the fractional time derivative ' α ' are discussed on the basis of the numerical results. Some earlier published results can be obtained without nonlocal parameters e 0 a .